Structure-based capacitance modeling and power loss analysis for the latest high-performance slant field-plate trench MOSFET. (23rd March 2018) - Kobayashi, Kenya; Sudo, Masaki; Omura, Ichiro
Abstract: Field-plate trench MOSFETs (FP-MOSFETs), with the features of ultralow on-resistance and very low gate–drain charge, are currently the mainstream of high-performance applications and their advancement is continuing as low-voltage silicon power devices. However, owing to their structure, their output capacitance ( C oss ), which leads to main power loss, remains to be a problem, especially in megahertz switching. In this study, we propose a structure-based capacitance model of FP-MOSFETs for calculating power loss easily under various conditions. Appropriate equations were modeled for C oss curves as three divided components. Output charge ( Q oss ) and stored energy ( E oss ) that were calculated using the model corresponded well to technology computer-aided design (TCAD) simulation, and we validated the accuracy of the model quantitatively. In the power loss analysis of FP-MOSFETs, turn-off loss was sufficiently suppressed, however, mainly Q oss loss increased depending on switching frequency. This analysis reveals that Q oss may become a significant issue in next-generation high-efficiency FP-MOSFETs.